Metaphyseal chondrodysplasia, neutropenia, and pancreatic insufficiency presenting with respiratory distress in the neonatal period. Issue 9 (September 1976) - Danks, D M; Haslam, R; Mayne, V; Kaufmann, H J; Holtzapple, P G
Abstract : Two pairs of brothers suffered respiratory distress in the newborn period because their ribs were abnormally short. The diagnostic radiological features of metaphyseal chondrodysplasia appeared only in the second year. Pancreatic insufficiency and neutropenia were present. One died of overwhelming infection and his brother survived a life-threatening episode of gangrenous proctitis.